Implementation of the Online Good Corporate Governance System in Indonesia - Marlina Widiyanti, Sulastri, Isnurhadi, Mohamad Adam (International Journal of Advanced Science and Technology, 2020)
Economic growth and development signifies rapid development for companies in Indonesia. This development is undeniable about the benefits of technology in human life. This study aimed to analyze the implementation of online good corporate system in home country. To get the data needed, this qualitative study used literature review and looks for related theories about Good Corporate Governance as the primary theory, while supporting data compare the Good Corporate Governance theory in several companies in Indonesia and companies in the world. The results of research conducted on companies that have a Good Corporate Governance system, including; First, the progress of a company is inseparable from the role of technology, has quality human resources, and there is cooperation between superiors and subordinates so that they are able to compete with other companies. Second, the progress and development of a company will not be able to survive if it does not complicate good financial management and implement the Good Corporate Governance system.